What is the expression #(x^2z^3)(xy^2z)# is equivalent to?

1 Answer
Aug 19, 2017

Answer:

See a solution process below:

Explanation:

We can rewrite the expression as:

#(x^2 * x)y^2(z^3 * z)#

Next, we can use these rules of exponents to multiply the #x# and #z# terms:

#a = a^color(blue)(1)# and #x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#

#(x^2 * x)y^2(z^3 * z) =>#

#(x^color(red)(2) * x^color(blue)(1))y^2(z^color(red)(3) * z^color(blue)(1)) =>#

#x^(color(red)(2)+color(blue)(1))y^2z^(color(red)(3)+color(blue)(1)) =>#

#x^3y^2z^4#